Standardised quantification of structural efficiency of hybrid reinforcement systems for developing concrete composites. (15th October 2021) - Gribniak, Viktor; Sultani, Haji Akbar; Rimkus, Arvydas; Sokolov, Aleksandr; Torres, Lluis
Highlights: A standardised layout proposed to form multiple cracks in a small laboratory sample. A simple approach for flexural stiffness analysis of reinforced concrete developed. The closed-form analytical solution enables the analysis of repeated load cases. Mechanic interlock bond systems are efficient for improving the residual stiffness. Exceptional efficiency of beams reinforced with CFRP and steel components observed. Abstract: Various types of materials and technologies have been developed either for reinforcing or strengthening concrete structures. However, there is no uniform methodology to quantify and compare the mechanical characteristics of different reinforcement systems. Residual stiffness of flexural elements is the suggested measure of the reinforcement's structural effectiveness, involving concrete into composite action. This manuscript proposes a new testing layout designed to form multiple cracks in a small laboratory specimen and a simplified analytical approach to quantifying the flexural stiffness of the standardised test samples. The achieved analytical solution to the stiffness problem requires neither iterative calculations nor the loading history description. That makes it acceptable for quantifying and comparing the residual stiffness of elements with various combinations of reinforcement materials. The proposed analysis procedure also enables determining the mechanical performance decay under repeated and long-term loading conditions without a loss of the calculation adequacy. Flexural tests illustrate the application of the proposed technique—the 38 specimens were mechanically loaded until failure. Several composite reinforcement schemes, including steel and glass fibre reinforced polymer (GFRP) bars, externally bonded carbon fibre (CF) sheets, and near-surface mounted (NSM) carbon fibre reinforced polymer (CFRP) strips in various combinations, are considered. The analysis reveals an exceptional efficiency of hybrid reinforcement systems, combining steel and CFRP components.